Associations of Fatigue with Quality of Life and Self-Efficacy in Adolescents with Type 1 Diabetes Mellitus: A Cross-Sectional Study - Nur Agustini; Allenidekania Allenidekania; Yulia Yulia (An Idea Health Journal, 2026)
Background: Fatigue is a common concern among adolescents with Type 1 Diabetes Mellitus (T1DM) and may affect their quality of life and disease management. However, the relationship between fatigue, quality of life, and self-efficacy remains insufficiently understood. This study aimed to examine the relationship between fatigue and quality of life and self-efficacy among adolescents with T1DM. Methods: A cross-sectional correlational study was conducted with 110 adolescents aged 10–19 years with T1DM. Diabetes-related quality of life was assessed using the PedsQL Diabetes Module, fatigue using the Short Fatigue Scale, and self-efficacy using the Pediatric Rating of Chronic Illness Self-Efficacy (PRCISE) scale. Spearman correlations and Chi-square tests were used for analysis. Results: The results showed that 82.7% of participants experienced fatigue, with 17.3% categorized as having severe fatigue. Fatigue was moderately negatively correlated with quality of life (r = −0.547, p < 0.001) and self- efficacy (r = −0.475, p < 0.001). A significant association was also found between gender and fatigue level (p = 0.029), with severe fatigue reported more frequently among females (24.2%) than males (8.3%). Conclusion: Fatigue among adolescents with T1DM is associated with lower quality of life, lower self-efficacy, and gender differences. Self-efficacy may play an important role in reducing fatigue and supporting adolescent well-being.